2017
DOI: 10.1016/j.mrrev.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus molecular biology

Abstract: Human papillomaviruses are small DNA viruses with a tropism for squamous epithelia. A unique aspect of human papillomavirus molecular biology involves dependence on the differentiation status of the host epithelial cell to complete the viral lifecycle. A small group of these viruses are the etiologic agents of several types of human cancers, including oral and anogenital tract carcinomas. This review focuses on the basic molecular biology of human papillomaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
177
1
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(202 citation statements)
references
References 130 publications
(136 reference statements)
0
177
1
24
Order By: Relevance
“…E4 binds to cytokeratin filaments, disrupting their structure, and is thought to play a role in viral escape from the desquamated epithelium (for review see ref. ).…”
Section: Hpv Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…E4 binds to cytokeratin filaments, disrupting their structure, and is thought to play a role in viral escape from the desquamated epithelium (for review see ref. ).…”
Section: Hpv Infectionmentioning
confidence: 97%
“…The ancient papillomaviruses with mucosal tropism started developing some 90 million years ago . During their evolution, human papillomaviruses (HPVs) developed, acquiring the capacity to utilize human cellular proteins for replication and to remain silent by hijacking the cellular and immune systems at several levels . The manifestations of HPV infections can be multiple, varying from asymptomatic infections to benign warty or potentially malignant lesions, intraepithelial neoplasia, and invasive carcinomas .…”
mentioning
confidence: 99%
“…to keep infected epithelial cells in a replication-competent state while they are differentiating. Not surprisingly, this behavior, as well as expression of the E7 oncogene, are sensed as abnormal, and the cell responds by triggering apoptosis and oncogene-induced senescence [81,82]. In fact, the high-risk HPVs have evolved to target p53 and RB1 and thus cause cancer hallmarks because p53 and RB1 are key mediators of apoptosis and senescence [83].…”
Section: The Connection Between Persistent Infection and Oncogenesismentioning
confidence: 99%
“…HIF‐1α overexpression has been associated with tumor cell growth and survival in head and neck tumors. Moreover, HPV is responsible for the rising proportion of OSCC and might induce the expression of oncogenes 27. Numerous expression and functional analyses have demonstrated that Notch1 plays a crucial role in the development and progression of OSCC 26.…”
Section: Discussionmentioning
confidence: 99%